2020
DOI: 10.1159/000509770
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Metastasis to the Breast: A Case Report and Review of the Literature

Abstract: Although ovarian cancer often presents as a widespread disease, metastases to the breast and/or axillary lymph nodes are a very rare event, accounting for only 0.03–0.6% of all breast cancers. Its early recognition and accurate distinction from primary breast cancer are of crucial importance to choose an adequate systemic therapy over unnecessary surgeries. We presented the case of a 53-year-old woman who was diagnosed with breast metastases 2 years after the diagnosis of advanced primary serous ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The most common sites of distant metastasis in ovarian cancers are the liver, followed by distant lymph nodes, lung, bone, and brain, respectively [ 17 ]. Ovarian cancers rarely metastasize to the breast [ 5 ]. Metastasis to the breast consists of only 2% of all breast malignancies, with ovarian cancer accounting for only 0.03 to 0.6% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common sites of distant metastasis in ovarian cancers are the liver, followed by distant lymph nodes, lung, bone, and brain, respectively [ 17 ]. Ovarian cancers rarely metastasize to the breast [ 5 ]. Metastasis to the breast consists of only 2% of all breast malignancies, with ovarian cancer accounting for only 0.03 to 0.6% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caruso et al reported 120 cases of ovarian cancer with breast metastasis between 1999 to 2019. Serous carcinoma of the ovaries is the most common histologic type of ovarian cancer metastases to the breast [ 5 ]. It was reported that there was a preference for metastasis to the left breast [ 5 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, in OC the role of immunotherapy is still uncertain, and results from immunotherapeutic agents administered alone are not as positive as expected, and nowadays, the use of immunotherapeutic drugs in OC is limited to clinical trials. Since few and ineffective chemotherapeutic agents are currently available for PtR OC, immunotherapeutic drugs, especially in combination with other agents [202][203][204][205][206][207], could represent a future successful strategy and change the prognosis of affected women. Consequently, the main challenge regarding the identification of populations that could benefit more from this approach and biomarkers that predict the response to this treatment deserves a separate discussion.…”
Section: Immune-related Biomarkersmentioning
confidence: 99%